Utilization of enzyme incubated rape seed meal as a source of protein in commercial broiler diets - RAO, S V RAMA; RAJU, M V L N; PRAKASH, B; VERMA, S K; RAJKUMAR, U; REDDY, E P K (The Indian Journal of Animal Sciences, 2017)
Two experiments were conducted to study the possibility of utilizing enzyme incubated rape seed meal (RSM) in broiler diets (1 to 42 day of age). The RSM was anaerobically incubated with non-starch polysaccharide hydrolyzing enzymes (cellulase 1,500 IU, xylanase 250 IU and pectinase 125 IU per kilogram) for 300 minutes (processed RSM1, experiments 1 and 2) and 600 min (processed RSM2, experiment 2). Processed and raw RSM contained similar concentration of glucosinolates (275 and 288 mM/g, respectively). During the experiment 1, maize-soybean meal control diet (CD), two diets with raw (RRSM) and processed RSM (PRSM1) at 100 g/kg each were prepared. In the experiment 2, RRSM, PRSM1 and PRSM2 were included each at 3 levels (50, 100 and 150 g/kg). Each diet was offered to 9 replicates having 5 birds in each. Body weight gain (BWG), feed intake (FI), feed efficiency (FE), ready to cook (RTC) yield and breast weight were depressed by incorporating RRSM (experiments 1, 2). As a result of this study, PRSM1 significantly reduced FI, maintained BWG and improved FE compared to the control group. BWG was not affected by including PRSM1 and PRSM2 up to 100 and 50 g/kg, respectively but depressed at higher inclusion levels compared to the CD. The BWG in processed RSM fed groups were higher than the respective level of raw RSM fed groups. Retention of energy and protein were improved by incorporating processed RSM compared to those fed RRSM. Based on the data, it is concluded that enzyme (cellulase, xylanase and pectinase) incubated RSM for 300 minutes improved the nutritional value, which can be incorporated up to 100 g/kg in broiler diet without affecting performance and slaughter variables, which can be attributed to the improved retention of energy and protein in RSM based diets.